"A Vibrant National Preoccupation": Embracing an Energy Conservation Ethic in the 1970s. Issue 1 (19th November 2019) - Wellum, Caleb
Abstract: This article examines the popularity of the "energy conservation ethic" in the United States during the 1970s, which environmentalists, politicians, and oil companies endorsed as a solution to the energy crisis. It demonstrates that broad support for an energy conservation ethic contained two competing paradigms: one "ecological" and the other "nationalist." The former advocated conservation as a means to a sustainable low-carbon future, while the latter viewed the conservation ethic as a tool to eliminate dependence on foreign oil in order to reestablish the economic and geopolitical strength of the United States. Thus, in contrast to a view that traces a relatively linear transition from the utilitarian and nationalist ethos of early twentieth-century conservationism to the more holistic concern with "the environment" of the postwar environmental movement, this article underscores the persistence of utilitarian conservationist conceptions of resource stewardship in the middle of the "environmental decade." These competing paradigms contributed to the argument for energy price deregulation as the most effective way to discipline US energy consumers. In this way, the energy crisis and the conservation debates that it evoked reflected the rightward turn of the United States in the 1980s. Current energy history tends to focus on the political, environmental, and socioeconomic histories of energy production and consumption rather than efforts to reduce demand but, as this article demonstrates, discourses of conservation can also shape political trajectories in unexpected ways.